Analysis of shopeepay usage intention among Bekasi high school students - Anggraini, Asterina; Sudarno, Sudarno; Wardhani, Annisa; Farhani, Nuraeni Hadiati; Harmuzan, Harmuzan (Institute of Accounting Research and Novation (IARN), 2026)
The development of financial technology (fintech) has fundamentally transformed societal transaction patterns from conventional systems to digital platforms, including among high school students who constitute part of Generation Z. Despite their high level of technological adaptability, the intention to utilize fintech services such as ShopeePay is influenced by various determining factors. The purpose of this study is to examine how high school students in Bekasi City's intention to use ShopeePay is influenced by perceived benefit, perceived risk, ease of use, and trust. Employing a quantitative approach with an associative research design, this study utilized a survey method through the distribution of Likert-scale questionnaires to high school students who are ShopeePay users. Multiple linear regression was used to analyze the data following validity, reliability, and traditional assumption tests. The results show that while perceived risk has a negative and significant impact on ShopeePay usage intention, trust, ease of use, and perceived benefit have a positive and significant impact. Ease of use emerged as the most dominant variable influencing usage intention, whereas perceived risk constituted the strongest inhibiting factor. These findings indicate that increasing ShopeePay usage intention among students necessitates strengthening security aspects, enhancing digital financial literacy, and providing accessible and beneficial services. This study provides empirical contributions to the development of technology acceptance models in the fintech sector among adolescent users.